Cross-cultural validation of acculturation measures: Expanding the East Asian acculturation framework for global applicability - Erhabor Sunday Idemudia; Constance Karing; Lawrence Ejike Ugwu (PLoS ONE, 2025)
In a globalised world, understanding acculturation, the process by which individuals adapt to new cultural environments, is crucial, especially in multicultural societies experiencing increased migration. The East Asian Acculturation Measure (EAAM), based on Berry’s acculturation model, has been a cornerstone for assessing acculturation strategies among East Asian populations in the United States; however, its cultural specificity limits utility in broader contexts. This study addresses this gap by adapting and validating the EAAM for diverse populations, producing the Shortened Adapted Acculturation Scale (SAAS). Across two phases involving 490 university students from 87 nationalities in Germany and 329 university students from 25 nationalities in South Africa, both Confirmatory Factor Analysis (CFA) and Exploratory Factor Analysis (EFA) identified a five-factor structure: Social Disconnection, cultural adaptation, Social Perception, Interpersonal Comfort, and Language Integration. The SAAS showed high internal consistency and measurement invariance across genders. These results highlight the importance of culturally adapting psychological measures to ensure their relevance and reliability in global contexts. The SAAS offers practical benefits for clinicians, educators, and policymakers who serve multicultural populations. By illuminating specific dimensions of acculturation, the scale can help identify areas where targeted interventions such as mental health counselling, cultural orientation programs, or inclusive campus policies may foster better social integration and well-being. Although the present study focused on structural validity, future research should examine the SAAS’s predictive utility for mental health and social integration outcomes. These findings contribute to cross-cultural psychology and underline the need to refine and validate tools for assessing acculturation in an increasingly interconnected world.